Nicholas of Cusa's On learned ignorance a commentary on 'De docta ignorantia' - Harries, Karsten 1937- (The Catholic University of America Press, 2024)
"This is the first commentary to have been written on Nicholas of Cusa's most famous work, On Learned Ignorance. This fact testifies to the difficulty of what has long been recognized to be the most significant philosophical text produced by the Renaissance. While there are many passages in the work that can be cited in support of Cassirer's celebration of Cusanus as the first modern philosopher, that judgment is challenged by the way his work is rooted in a faith and a tradition likely to strike us as thoroughly medieval. This commentary shows how closely the two are linked. Despite the many ways in which what the cardinal has to say belongs to a past that the progress of reason would seem to have left irrecoverably behind, it yet provides us with a continuing challenge. Key to On Learned Ignorance is the incommensurability of the infinite and the finite, of God and creation. Cusanus lets us recognize the essential transcendence of reality, so different from the ontology implied by Descartes' insistence on clear and distinct understanding, which has presided over the progress of science and has helped shape our world. What makes Cusanus' thought important is not the way it anticipates modernity, but the way it challenges often taken-for-granted presuppositions of our worldview, most importantly a distinctly modern self-assertion or self-elevation that has made our human reason the measure of reality. If it is impossible to deny the countless ways in which our science and technology have given us ever deeper insights into the mysteries of nature and improved our lives, it is equally impossible to deny that this very progress today endangers this fragile earth and the quality of our lives. Cusanus can help us preserve our humanity."--
Keywords: Nikolaus -- von Kues, Kardinal -- 1401-1464 -- De docta ignorantia; Nicholas / of Cusa, Cardinal / 1401-1464 / De docta ignorantia / English; Nicholas / of Cusa, Cardinal / 1401-1464 / Criticism and interpretation; Ontology; God (Christianity); Trinity; Jesus Christ / Divinity; Truth / Religious aspects / Christianity; Cosmology; Philosophy, Medieval; Ontologie; Dieu (Christianisme); Trinité; Vérité / Aspect religieux / Christianisme; Cosmologie; Philosophie médiévale; Jésus-Christ / Divinité; ontology (metaphysics); cosmology; Kommentar